Regulation of T-Cell Immune Responses by Pro-Resolving Lipid Mediators - Perez-Hernandez, Javier; Chiurchiù, Valerio; Perruche, Sylvain; You, Sylvaine (Frontiers in Immunology, 2021)
Both the initiation and the resolution of inflammatory responses are governed by the sequential activation, migration and control/suppression of immune cells at the site of injury. Bioactive lipids play a major role in the fine tuning of this dynamic process in a timely manner. During inflammation and its resolution, polymorphonuclear cells (PMNs) and macrophages switch from producing pro-inflammatory prostaglandins and leukotrienes to specialized pro-resolving lipid mediators (SPMs), namely lipoxins, resolvins, protectins and maresins, which are operative at the local level to limit further inflammation and tissue injury and restore homeostasis. Accumulating evidences expand now the role and actions of these lipid mediators from innate to adaptive immunity. In particular, SPMs have been shown to contribute to the control of chronic inflammation and alterations in their production and/or function have been associated with the persistence of several pathological conditions, including autoimmunity, in human and experimental models. In this review, we focus on the impact of pro-resolving lipids on T cells, through their ability to modulate T-cell responses. In particular, the effects of the different families of SPMs to restrain effector T-cell functions while promoting regulatory T cells will be reviewed, along with the underlying mechanisms. Furthermore, the emerging concept of SPMs as new biological markers for disease diagnostic and progression, and as putative therapeutic tools to regulate the development and magnitude of inflammatory and autoimmune diseases is discussed.